1987
DOI: 10.1530/jrf.0.0810479
|View full text |Cite
|
Sign up to set email alerts
|

Change in the relative importance of oestrone and oestradiol synthesis by the rat ovary between fetal and prepubertal stages

Abstract: Ovaries of rat fetuses at 20 and 21 days and of neonatal rats at 5 and 14 days were cultured in the presence of [3H]testosterone, and the conversion percentages into oestrone (E1) and oestradiol (E2) were determined by double isotopic dilution combined with recrystallization to constant specific activity. Insignificant in the 20- or 21-day-old fetus, oestradiol synthesis increased relative to oestrone synthesis in the 5-day-old neonate (E1/E2 = 3.4) and still more at the stage of 14 days (E1/E2 = 0.78). FSH ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…Production of E 2 by the ovary was low and was not affected by either the gonadotropin treatment in vivo or the subsequent short-time incubation in vitro with gonadotropins. This is consistent with previous studies in which perinatal rat ovaries below the age of 11 days did not respond to gonadotropins with production of E 2 [21,42]. However, aromatase activity has been shown in cultured ovaries in the presence of androgen precursors even at the age of 4-5 days [18,40,43], and the activity increases during the first two postnatal weeks [44].…”
Section: Discussionsupporting
confidence: 92%
“…Production of E 2 by the ovary was low and was not affected by either the gonadotropin treatment in vivo or the subsequent short-time incubation in vitro with gonadotropins. This is consistent with previous studies in which perinatal rat ovaries below the age of 11 days did not respond to gonadotropins with production of E 2 [21,42]. However, aromatase activity has been shown in cultured ovaries in the presence of androgen precursors even at the age of 4-5 days [18,40,43], and the activity increases during the first two postnatal weeks [44].…”
Section: Discussionsupporting
confidence: 92%
“…In none of 3 successive studies could stimulation of aromatase activity by FSH be demon¬ strated unequivocally (Weniger et al, 1985;Weniger & Zeis, 1987b, 1988b. Nor did George & Ojeda (1987) notice any augmentation of aromatase activity in 19-22-day-old fetal rat ovaries treated with FSH.…”
Section: Action Of Fsh and Campmentioning
confidence: 94%
“…However, this hypothesis loses strength because chick embryo ovaries cultured under the same conditions as used in the fetal rat ovary produced mainly oestradiol (Weniger et al, 1983). It can be dismissed in view of the results obtained when culturing fetal rat ovaries in Medium 199, in which synthesis was almost exclusively of oestrone (Weniger & Zeis, 1987b). This result was confirmed independently by Picon et al (1985), who found that oestrone production was 12-fold that of oestradiol.…”
Section: Introductionmentioning
confidence: 97%